Investigating Factors Affecting reliance on electronic banking services from the customers’ point of view: A case study of the Libyan banking sector (Journal of Academic Research, 2023)
This study aimed to expand the scope of the literature by providing exploratory evidence on the factors influencing reliance on electronic banking services from the perspective of customers within Libyan commercial banks. The relevant hypotheses were tested by analysing the data collected from the questionnaire distributed to a random sample. A sample of clients of Libyan commercial banks. The study sample was (322) individuals, and after conducting statistical analysis, the study reached a set of results, the most important of which is customers’ lack of confidence in electronic banking services, and customers also have concerns about the presence of potential risks. . And in electronic banking services, the results showed regarding... ease of use for customers in electronic banking services. There are no clear instructions and directions on the bank’s website on how to use it correctly or explanations and illustrative examples to facilitate the process of using electronic services. On the other hand, the study showed that the possibility of risks also greatly affects the demand for banking services. Electronically - where customers are extremely concerned about the potential for loss of personal data, hacking and fraud.
Keywords: banking services, factors affecting services, Libyan banking sector